1993
DOI: 10.1172/jci116564
|View full text |Cite
|
Sign up to set email alerts
|

Contractile elements and myosin light chain phosphorylation in myometrial tissue from nonpregnant and pregnant women.

Abstract: Smooth muscle contraction is initiated primarily by an increase in intracellular Ca2", Ca2+-dependent activation of myosin light chain kinase, and phosphorylation of myosin light chain. In this investigation, we identified pregnancy-associated alterations in myosin light chain phosphorylation, force of contraction, and content of contractile proteins in human myometrium. Steady-state levels of myosin light chain phosphorylation and contractile stress were correlated positively in both tissues, but the myometri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
69
0
4

Year Published

1995
1995
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(81 citation statements)
references
References 51 publications
8
69
0
4
Order By: Relevance
“…Band densities were quantitated by using a phosphor imager. Consistent with a previous report where CaD levels were measured in human tissue (39), the CaD protein level is significantly increased during pregnancy in rat myometrium (Fig. 3B, n ϭ 30).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Band densities were quantitated by using a phosphor imager. Consistent with a previous report where CaD levels were measured in human tissue (39), the CaD protein level is significantly increased during pregnancy in rat myometrium (Fig. 3B, n ϭ 30).…”
Section: Resultssupporting
confidence: 93%
“…An increased protein level of CaD in term pregnant human myometrium compared with nonpregnant human myometrium has been reported (39). However, the contractile correlate of the increased CaD level has not been determined and whether CaD's inhibitory action may be reversed by ERK1/2-dependent phosphorylation in a gestation-related manner has not been explored.…”
mentioning
confidence: 99%
“…Others, including calponin and h-caldesmon, modulate the actomyosin complex (13,14). Previous studies have shown that expression levels of contractile apparatus proteins increase with pregnancy (15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…By either mechanism, CaD negatively regulates the actomyosin interaction and acts as a molecular brake. 141 …”
Section: Biochemical Properties and Regulatory Functionsmentioning
confidence: 99%